Intended consequences : how to build market-leading companies with responsible innovation - Taneja, Hemant; Maney, Kevin, 1960- (McGraw Hill, 2022)
"The old Milton Friedman philosophy that companies exist only to increase shareholder value is dying. The most successful companies will increase the value of life on this planet. ESG (environmental, social, and corporate governance) are measurements. But how do you build a company so that it ranks high in ESG, adheres to those ideals, and performs better than companies that don't? In The End of Unintended Consequences, Hemant Taneja: lays out the argument for why a new model of company building is necessary-and how it can lead to better performance vs. operating in less-aware ways explores why social-good businesses are some of the greatest opportunities today, detailing examples of billion-dollar startups that are addressing inequality, climate change, systemic societal problems, and chronic individual problems provides a topic-by-topic guide that addresses business models, artificial intelligence, ethical growth, culture, governance, and good citizenship. A company's mindset-its intent to do good, avoid harmful consequences, and innovate responsibly-is not enough. The mindset must be supported by a mechanism, a business model that rewards the company for sticking to its mindset. Otherwise, pressure to financially perform will threaten the mindset. Companies need a new set of KCIs, or key consequence indicators that measure factors such as its impact on others' energy use, whether its product is being used equally across socioeconomic groups, or if the social problem it is solving is actually getting solved. To avoid biases or other consequences of AI, companies must also build "algorithmic canaries" that can monitor its own AI and watch for signs of misuse. The old tenets that used to drive the tech industry-move fast and break things, minimum viable products, engagement, hypergrowth-need to be replaced with new tenets for an era of responsible innovation that will fuel the companies that will succeed in the future. The End of Unintended Consequences is designed as the ultimate guide for founders, entrepreneurs, leadership teams, and investors on how to build and maintain a responsible innovation company"--